KAJIAN MOLEKULER GEN PROTEKTIF ANTIGEN Bacillus anthracis ISOLAT INDONESIA - SANAM, MAXS URIAS EBENHAIZAR ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Bacillus anthracis is a rod-shaped, gram-positive, spore-forming bacteria that causing anthrax in animals, especially herbivores, and in humans. Anthrax is spread in many countries around the world including a number of provinces in Indonesia. The virulence of B.anthracisis determined by two virulence plasmid namely, the pXO1 containing genes encoding anthrax toxins, and the pXO2 which encodes for the formation of bacterial capsule. Protective antigenic gene (PagA) located on pXO1 encodes for antigenic protein (PA) which is immunogenic and plays an important role in the pathogenesis of anthrax. Data on pagA gene sequences of isolates from Indonesia is very limited and the variation of their genotypes has not been disclosed. This study aims to reveal the model, genotypes, sequences and phylogenetic relationships of pagA gene of B. anthracisi solates from Indonesia. Twenty-seven anthrax-related isolates of Central Java, Yogyakarta, East Nusa Tenggara, West Nusa Tenggara and Papua were studied and their DNA was extracted by heat lysis method, followed by PCR and sequencing reactions. Aligned sequences were obtained and compared to a number of reference sequences of B. anthracis and B.cereus strain derived from GenBank. Visualization of multiplex PCR products revealed 2 isolates had lost either pXO1 or pXO2. Three primer pairs PA8 / PA5, PA1846F / PA2443R and PA5F / PA5 R respectively used to amplify and sequence partial gene of PagA. The results of sequence alignment with ClustalW method of MEGA5 software revealed a high degree of homogeneity. However five isolates from NTT and NTB were found to have two point mutations at nucleotide positions of 195 and 1799 which then be classified as genotype 5. Meanwhile, none of the rest nineteen isolates has point mutation or single nucleotide polymorphism (SNP) and therefore being grouped as pagA genotype 1. Phylogenetic analysis conducted with UPGMA methode produced 2 clusters, namely B. anthracis and B. cereus pXO1-like clusters. In B. anthracis cluster, the two groups of genotype occupy different subclusters. Based on the results obtained it can be concluded that in Indonesia there are 2 PagA genotypes of B. anthracis strains of which the dominant type is the genotype 1 (79%) and genotype 5 (21%). It was also concluded that the pagA sequences of B. anthracis is significantly distinguishable from that of B. cereus pXO1-like strains which is being classified as genotype 9.